Factors associated with depression, anxiety and stress among dentists the COVID-19 pandemic - Alencar, Cristiane De Melo [UNESP]; Silva, Aryvelto Miranda [UNESP]; Jural, Lucas Alves; Magno, Marcela Baraúna; Campos, Edson Alves De [UNESP]; Silva, Cecy Martins; Coqueiro, Raildo Da Silva; Pithon, Matheus Melo; Maia, Lucianne Cople (FapUNIFESP (SciELO), 2021)
The objective of this work was to evaluate the relationship between factors associated with the COVID-19 pandemic and depression, anxiety, and stress (DAS) in dentists. Factors associated with the COVID-19 pandemic were evaluated using a questionnaire and scores of the Depression, Anxiety, and Stress Scales-21 were measured. The differences between the DAS scores based on the factors associated with the COVID-19 pandemic were tested through the successive application of multivariate analysis of variance (MANOVA, α = 0.05). After a sample size calculation, 998 participants with a mean age of 39.39 (± 11.69) years were included. The effect size indicated that changes in sleep quality (η2 = 0.161), eating habits (η2 = 0.057), and physical health (η2 = 0.051) were the ones that most negatively affected DAS scores. The highest DAS scores were COVID-19 (p < 0.001) and in those who did not engage in leisure activities during the pandemic (p < 0.001). Dentists who worked on the frontline against COVID-19 had higher scores of anxiety and stress (p = 0.029). The highest scores for anxiety, depression, and/ or stress were seen in dentists living with someone at high-risk for COVID-19, who acts on the frontline, who does not practice in leisure activities during the pandemic, who completely changed eating habits, quality of sleep and physical health during the pandemic. In general, DAS levels of dentists were associated with factors related to the COVID-19 pandemic.
Keywords: Anxiety; COVID-19; Dentists; Depression; Psychological; Stress